Repenser les liens entre Bruxelles et son port : un enjeu d’aménagement pour la zone du Canal - Kristel Mazy (Brussels Studies)
Due to a flexible and cross-cutting approach, the urban project is emblematic of contemporary urbanistic concepts. Can this approach reconnect cities, ports and waterways? On the contrary, can it reinforce the disconnection under way, in a context in which the rationale of the market is more favourable to the sphere of residential economy than to the sphere of productive economy? This question is raised especially with respect to the canal area of Brussels, where major challenges intersect: urban densification in a context of demographic growth, the transferring of river freight as a sustainable alternative to the road network, and the improvement of water management. The aim of this article is to understand the evolution of the relationship between city and port via the interactions of the projects of the different stakeholders concerned. By means of a spatial and temporal approach, the results show that through their materialisation, the projects contribute to reproducing the functional divisions of the industrial era, caused by their economic environment. However, through their processes, new frameworks for a dialogue between city and port emerge. These observations provide some ideas for a reconnection between the city and its port.